Migrant Workers Empowerment Through Vocational Education and Community-Based Learning: A Study Case of Indonesian in Taiwan - Paulus Rudolf Yuniarto (Journal of Indonesian Social Sciences and Humanities, 2019)
Based on the observation of Indonesian migrant workers vocational training programs and community-based learning activities in Taiwan, the training programs play a part in assisting migrant workers to improve their skill and develop self-capacity building, to facilitate knowledge transfer and offer guidelines on productive financial management to migrant workers, and to introduce and develop intercultural communication with locals. However, financial and material support from stakeholders (government and communities) to develop skills and building an institution that can bridge migrants and stakeholders are still underdeveloped. Various constraints ranged from the large number of migrants, voluntary absences, lack of material support, under-qualified teachers, limited business skill training, and limited networking are challenges that need to be addressed. In addition, vocational education/training curriculum are old fashioned and exclusive (segmented, only for active and bright worker). In the future development, it is vital to support more on community-based education/training programs and open access to a life skill education (knowledge) that can increase the worker’s self-esteem or self-transformation (a semblance of future carrier).